Possible forms of parenthood in the rhetoric of silence (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper examines the Italian Constitutional Court’s decision of January 28, 2021, no. 32, from a rhetorical perspective, focusing on textuality, syntax, lexicon, and argumentation. The study operates on three levels: first, it addresses legal language and the relationship between language and law; second, it explores the rhetorical perspective, defining rhetoric and its techniques within the contemporary debate; third, it analyzes the rhetorical concept of kairòs in the judgment. This approach highlights the interplay between rhetoric and legal decision-making, offering a comprehensive understanding of the court’s reasoning.
Keywords: Rhetoric; Argumentation; Legal Language; Medically Assisted Procreation; Genitoriality